Self-Help Group-Based Awareness of Cervical Cancer Screening - A Narrative Review - Achita Sawarkar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
In India, one of the most prevalent malignancies affecting women is cervical cancer.1 Women's access to treatment and palliative care, as well as their knowledge of primary and secondary prevention techniques, need to be improved in order to prevent and control it. A focused strategy is required to eradicate cervical cancer before the World Health Organization's 2030 deadline. 12 By using tests, examinations, or other quickly applied processes, screening encourages the identification of undiagnosed diseases or problems.3 The ability to conduct screening tests with a significant number of participants and the availability of facilities capable of carrying out follow-up care, diagnosis, and treatment are both necessary for the screening process to be successful.4